ANALYSIS OF FACTORS AFFECTING OUTSOURCING WORKING AT AN AIRLINE IN TANGERANG: A GROUNDED THEORY STUDY APPROACH - Ainun Safangati (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2022)
Outsourcing becomes a problem or solution for a company. The company chooses outsourcing power intending to minimize production costs. On the one hand, this can benefit the company because it can reduce the cost associated with resources. After all, the company does not need to think about employees from upstream to downstream. Although this can sometimes be detrimental to the company itself if the outsourcing personnel does not have good abilities and skills at work because they have to do repeated processes in choosing the desired workforce and turnover of outsourcing is very high. This also applies to outsourcing personnel who work in the company, especially for outsourcing personnel who have worked for many years and showed good performance but were never appointed as permanent employees. This research aims to find reasons and factors that cause a person to become an outsourcing worker at PT Citilink Indonesia. This research uses a qualitative approach of Grounded Theory with data collection techniques to conduct interviews with outsourcing personnel. The results of the analysis showed that someone chose to become an outsourcing worker at Citilink Indonesia because of the factors of a comfortable and conducive work environment. Besides that, the career opportunity factor was also a consideration for outsourcing personnel working at PT Citilink Indonesia. It should be a special consideration for the human capital division of PT Citilink Indonesia to provide regular career opportunities for outsourcing personnel who have skills that are needed by Citilink Indonesia companies.